Chloride-induced corrosion modelling of cracked reinforced SHCC - Paul, Suvash Chandra (2017)
Corrosion of steel bars in concrete is usually a slow electrochemical process which may need a long time before damage becomes visible in the reinforced concrete (RC). However, cracks provide quick access to chloride, oxygen and water into concrete and accelerate the corrosion process. Corrosion modelling is essential for structural design for a particular life span, or to inform decisions on repair of RC structures to reach or extend their service life. This paper reports experimental research results of accelerated chloride exposure of cracked reinforced strain hardening cement-based composite (R/SHCC) specimens for a period of one year. Based on these novel results, a corrosion model is proposed which incorporates crack width, crack spacing, free chloride content and cover depth. The model is shown to capture the corrosion results of cracked R/SHCC reported in this paper.